The Influence of Job Stress and Job Conflict on Job Satisfaction - Mochamad Fickrie Alfian (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Some of the components of human resource management are job stress and job conflict. Job stress is important to pay attention to because it will have an impact on job satisfaction and job conflict to maintain relationships with colleagues. The purpose of this study was to determine the magnitude of the influence partially or simultaneously job stress and job conflict on job satisfaction in grabbike driver-partners in Bandung. The method used is descriptive analysis and verification. The data collection technique used is a literature study and distributing questionnaires with 88 respondents. The analytical method used is path analysis using SPSS 24.0 software. Based on the results of the research, the following findings were obtained: job stress on grabbike partners can be said to be quite good, besides that, job conflicts on grabbike partners are quite good and job satisfaction on grabbike partners is quite good. Partially job stress affects job satisfaction and job conflict affects job satisfaction. Also, simultaneously job stress and job conflict affect job satisfaction. These results suggest drivers not to cancel orders if they get orders, and drivers should improve their performance by not making picky orders so that they will get a greater chance of getting stable orders.